Probiotics as feed additives - Zeynep Erdoğan (Eurasian Journal of Veterinary Sciences)
Antibiotics and hormones have been using as feed additives in different ways to provide high performance. It is also known that they have some unwanted side effects for animal and humans. Alternatively, probiotics which are living microorganisms, can be added to animal diet to utilize their stimulation ol growth performance, anti-infectious effects and treatment of digestive track disorders.